Priority Analysis on the Reliability Parameters of an Existing Model - Khodaei, Seyed Hossein; Hassan, Adnan; Galankashi, Masoud Rahiminezhad (International Journal of Industrial Engineering and Management, 2014)
The basic goal of this paper is to create an alternative based analysis in a reliability model. Despite the vast amount of studies on reliability analysis and related techniques, the evaluation of the importance of different alternatives is less investigated. In order to fill this gap, this research was carried out to systematically investigate the result of setting three different scenarios on a reliability model. A model of reliability system was proposed based on redundancy allocation problems. There are certain limitations (Weight and Cost)of proposed model. In particular, three different scenarios (the results of Failure Rate preference, Weight preference and Cost Preference) was presented. This investigation operated based on the assumption of allocating only one redundant component for the subsystems, and the main goal of this investigation is to determine what would be the results when lowest possibleWeight, lowest possible Cost and lowest possible failure rate is needed. Article history: Received (23.03.2014); Revised (19.06.2014); Accepted (28.06.2014)